World Seas: An Environmental Evaluation Volume I: Europe, The Americas and West Africa - Hamel, Jean-Francois; Hamel, Jean-Francois (Academic Press, 2018)
World Seas: An Environmental Evaluation, Second Edition, Volume One: Europe, The Americas and West Africa provides a comprehensive review of the environmental condition of the seas of Europe, the Americas and West Africa. Each chapter is written by experts in the field who provide historical overviews in environmental terms, current environmental status, major problems arising from human use, informed comments on major trends, problems and successes, and recommendations for the future. The book is an invaluable worldwide reference source for students and researchers who are concerned with marine environmental science, fisheries, oceanography and engineering and coastal zone development. - Covers regional issues that help countries find solutions to environmental decline that may have already developed elsewhere - Provides scientific reviews of regional issues, thus empowering managers and policymakers to make progress in under-resourced countries and regions - Includes comprehensive maps and updated statistics in each region covered